The Status of Bank Lending to SMEs in the Middle East and North Africa Region : Results of a Joint Survey of the Union of Arab Bank and the World Bank - Rocha, Roberto; Farazi, Subika; Khouri, Rania; Pearce, Douglas (2012)
Among the principal constraints for SME lending is the lack of SME transparency, poor credit information from credit registries and bureaus, and weak creditor rights. If constraints can be addressed, lending can potentially reach bank targets of 21 percent. State banks still play an important role in financing SMEs in the MENA region, but they use less sophisticated risk management systems than private banks. On another hand, credit guarantee schemes are a popular form of support to SME finance in the region, and are associated with higher levels of SME lending. The paper concludes that MENA policy makers should prioritize improvements in financial infrastructure, including greater coverage and depth of credit bureaus, improvements in the collateral regime (especially for movable assets), and increased competition between banks and also non-banks. Weaknesses in insolvency regimes and credit reporting systems should also be alleviated. Direct policy interventions through public banks, guarantee schemes, lower reserve requirements and subsidized lending and other measures have played a role in compensating for MENA's weak financial infrastructure, but more sustainable structural solutions are needed.